2006
DOI: 10.1016/j.neuroscience.2006.08.039
|View full text |Cite
|
Sign up to set email alerts
|

A vital role for voltage-dependent potassium channels in dopamine transporter-mediated 6-hydroxydopamine neurotoxicity

Abstract: Abstract6-hydroxydopamine (6-OHDA), a neurotoxic substrate of the dopamine transporter (DAT), is widely used in Parkinson's disease models. However, the molecular mechanisms underlying 6-OHDA's selectivity for dopamine neurons and the injurious sequelae that it triggers are not well understood. We tested whether ectopic expression of DAT induces sensitivity to 6-OHDA in non-dopaminergic cortical neurons and evaluated the contribution of Kv channel-dependent apoptosis to the toxicity of this compound in cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Dopaminergic neurons contain significant levels of DA, hydrogen peroxide and free iron that can lead to 6-OHDA formation through a nonenzymatic reaction between these elements [9]. Some studies suggest that 6-OHDA needs to be internalized by DAT to produce its cytotoxic effect [38, 39]. However, extracellular auto-oxidation of 6-OHDA was reported to induce oxidative stress and apoptosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic neurons contain significant levels of DA, hydrogen peroxide and free iron that can lead to 6-OHDA formation through a nonenzymatic reaction between these elements [9]. Some studies suggest that 6-OHDA needs to be internalized by DAT to produce its cytotoxic effect [38, 39]. However, extracellular auto-oxidation of 6-OHDA was reported to induce oxidative stress and apoptosis [10].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that interfering with ASK-1 function, required for Kv2.1-mediated K 1 current surge (Aras and Aizenman, 2005), attenuated cell death. Finally, overexpression of a DN vector for Kv2.1, the K 1 channel responsible for mediating neuronal apoptosis in cortical, midbrain dopaminergic, and cerebellar granule neurons (Jiao et al, 2007;Pal et al, 2003;Redman et al, 2006), was also highly neuroprotective. Taken together, these results demonstrate that microglial-derived reactive species induce neuronal cell death via a process that involves the release of Zn 21 from intracellular sources, ASK-1 activation, and a surge in Kv2.1-mediated voltage-gated K 1 currents.…”
Section: Microglial-induced Neuronal Cell Deathmentioning
confidence: 97%
“…Blocking K ϩ channels, or increasing the extracellular K ϩ concentration, effectively attenuate cell death in many apoptotic models (2)(3)(4)(5)(6), including oxidant exposure in cortical and midbrain dopaminergic neurons (7)(8)(9)(10). With the use of dominant negative mutant subunits, Kv2.1, the major component of the delayed rectifier K ϩ current in neurons (11,12), was identified as the channel responsible for mediating the apoptotic K ϩ current surge in cortical neurons (13).…”
mentioning
confidence: 99%